Identifikasi Potensi Wisata Di Kampung Nelayan Tradisional Desa Lamalera - Batafor, Edel Meriquin Dai; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p13, 2018)
The village of Lamalera has great tourism potential to develope as a tourist attraction. However, it is important to consider some aspects in its development, such asaspect of the environment and the community, so that it will beneficial to the environment and can improve the economy of the community . The problem in this research was the potential of Lamalera, traditional fishing village. Data obtained in this study through observation, interview and documentation. The data were analyzed in qualitative descriptive by describing the potentials of Lamalera, traditional fishing village. The results showed physical and non physical potential of the village. The physical potential of Lamalera is white sandy beaches, crystal clear sea water, undersea view and other beauty of nature; while the non physical potential is in the form of custom ceremonial, traditional dances and religious.   Keywords : Identification, Potential and Tou rism